FKBP51 increases the tumour‐promoter potential of TGF‐beta. Issue 1 (27th January 2014) - Romano, Simona; D'Angelillo, Anna; D'Arrigo, Paolo; Staibano, Stefania; Greco, Adelaide; Brunetti, Arturo; Scalvenzi, Massimiliano; Bisogni, Rita; Scala, Iris; Romano, Maria Fiammetta
Abstract: Background: FKBP51 (FKBP5 Official Symbol) is a large molecular weight component of the family of FK506 binding proteins (FKBP). In recent years, research studies from our laboratory highlighted functions for FKBP51 in the control of apoptosis and melanoma progression. FKBP51 expression correlated with the invasiveness and aggressiveness of melanoma. Since a role for TGF‐β in the enhanced tumorigenic potential of melanoma cells is widely described, we hypothesized a cooperative effect between FKBP51 and TGF‐β in melanoma progression. Methods: SAN and A375 melanoma cell lines were utilized for this study. Balb/c IL2γ NOD SCID served to assess the ability to colonize organs and metastasize of different cell lines, which was evaluated by in vivo imaging. Realtime PCR and western blot served for measurement of mRNA and protein expression, respectively. Results: By comparing the metastatic potential of two melanoma cell lines, namely A375 and SAN, we confirmed that an increased capability to colonize murine organs was associated with increased levels of FKBP51. A375 melanoma cell line expressed FKBP51 mRNA levels 30‐fold higher in comparison to the SAN mRNA level and appeared more aggressive than SAN melanoma cell line in an experimental metastasis model. In addition, A375 expressed, more abundantly than SAN, the TGF‐β and the pro angiogenic TGF‐β receptor type III (TβRIII) factors. FKBP51 silencing produced a reduction of TGF‐β and TβRIII gene expression in A375 cell line, in accordance with previous studies. We found that the inducing effect of TGF‐β on Sparc and Vimentin expression was impaired in condition of FKBP51 depletion, suggesting that FKBP51 is an important cofactor in the TGF‐β signal. Such a hypothesis was supported by co immunoprecipitation assays, showing that FKBP51 interacted with either Smad2, 3 and p300. In normal melanocytes, FKBP51 potentiated the effect of TGF‐β on N‐cadherin expression and conferred a mesenchymal‐like morphology to such round‐shaped cells. Conclusions: Overall, our findings show that FKBP51 enhances some pro oncogenic functions of TGF‐β, suggesting that FKBP51‐overexpression may help melanoma to take advantage of the tumor promoting activities of the cytokine.